Cows' milk protein-sensitive enteropathy. Combined clinical and histological criteria for diagnosis. Issue 1 (January 1978) - Iyngkaran, N; Robinson, M J; Prathap, K; Sumithran, E; Yadav, M
Abstract : Cows' milk protein enteropathy is recognised as a significant cause of persistent diarrhoea and malabsorption in young infants, but there are as yet no generally accepted diagnostic criteria. A combined clinical and histological approach to the diagnosis of cows' milk protein-sensitive enteropathy has been used in 15 patients, and the following set of criteria are proposed. (1) Clinical disease (diarrhoea with or without vomiting) while receiving cows' milk protein. (2) Clinical improvement on a diet free of cows' milk protein. (3) Normal or mildly abnormal histology of jejunal mucosa when taken 6-8 weeks after symptoms subside. (4) Histological relapse, with or without clinical relapse, after re-exposure to cows' milk protein.